Membangun Brand Personality dan Brand Interaction terhadap Purchase Intention melalui Customer Satisfaction pada Produk Safi di Kota Semarang - Fida Intan Feriyana; Asyhari Asyhari; Wuryanti Wuryanti (Jurnal Simki Economic, 2025)
Sales data on the Safi brand on several e-commerce sites show a decline in sales and are uneven, this is due to increasingly tight market competition. The purpose of this study is to be used to build brand personality and brand interaction with purchase intention through customer satisfaction on Safi products in Semarang City. For this study, the purposive sampling method was used, which means that samples were taken based on predetermined criteria in accordance with the objectives of the study. The number of samples taken was one hundred respondents. This study will test the validity and reliability of the scale, the classical assumption test, and the multiple regression and Sobel tests to determine how the intervening variables relate to the independent variables and dependent variables. The results of this study indicate that brand personality and interaction with the brand have a positive and significant effect on customer satisfaction. The results of other analyses indicate that brand personality, interaction with the brand, and customer satisfaction have a positive and significant effect on purchase intention.